IMPACT OF COVID-19 ON POST NATAL MENTAL HEALTH - Nabia Tariq,; Maria Habib,; Ayesha Tariq,; Mishaal Noor,; Ayesha Jamal, (Journal of Ayub Medical College Abbottabad, 2021)
Background: In January, 2020 COVID-19 infection was declared a public health emergency characterized as pandemic by the World Health Organization (WHO). In March 2020, special guidelines were issued to address mental and psychological aspects of the disease survivors and community at large. This study was conducted with the aim to evaluate the psychological impact of COVID-19 on mothers in the postpartum period. Methods: It was cross-sectional study of six months duration on COVID-19 positive deliveries and Covid negative mothers. A total of 84 women (42 Covid Positive and 42 Covid negative) were included through non-probability quota with consecutive sampling technique. Mothers with pre-existing mental health issues, those who had been on medication for any psychological issues or those who suffered from obstetrical and neonatal complications or required transfer to High Dependency Unit (HDU) were excluded from the study. The Edinburgh Postnatal Depression Scale (EPDS) was used to screen the women for postpartum depression. Independent sample t test was used for continuous variables and Fisher exact test was used for qualitative variables. Results: Mean EPDS score was 9.48±6.33 in COVID-19 positive group. The sub-scale analysis showed mean scores 1.6±1.76 and 4.86±2.94 for Anhedonia and Anxiety with statistically significant difference. Conclusion: Women experiencing COVID-19 infection during pregnancy were found to have greater anxiety and nervousness in post-natal period compared to their COVID-19 negative counterparts